Clinical effects of supragingival plaque control on uncontrolled type 2 diabetes mellitus subjects with chronic periodontitis - Andrea Son; Claudia Pera; Paulo Ueda; Renato Corrêa Viana Casarin; Suzana Peres Pimentel; Fabiano Ribeiro Cirano (Universidade Estadual de Campinas, 2015)
Aim: To determine the clinical changes occurred in chronic periodontitis patients presenting uncontrolled type 2 diabetes mellitus after a supragingival plaque control period. Methods: Subjects presenting generalized chronic periodontitis were divided into two groups: Non-diabetics (n=20) - healthy subjects presenting chronic periodontitis; and Diabetics (n=14) - subjects with uncontrolled type 2 diabetes mellitus presenting chronic periodontitis. All subjects went through 28 days of supragingival plaque control - ST - (including prophylaxis, calculus removal, extraction of hopeless teeth and oral hygiene instructions) and were evaluated at baseline and after 28 days by the following parameters: Full-Mouth Plaque Score (FMPS) and Full-Mouth Bleeding Scores (FMBS), Periodontal Probing Depth (PPD), Gingival Recession (GR) and Clinical Attachment Level (CAL). ANOVA/Tukey's test and Student's t test were used for data analysis. Results: No statistically significant differences (p>0.05) between groups were observed at baseline for any parameter. Both groups presented a significant reduction in FMPS and FMBS after 28 days (p<0.05), but no statistically significant difference was found (p>0.05) between groups. Clinically, only the Non-diabetic group showed a significant improvement after ST, in PPD of initially deep pockets (p<0.05). However, no change in the clinical parameters was observed in the diabetic subjects (p>0.05). Conclusions: It may be concluded that uncontrolled diabetes mellitus reduces periodontal changes in the supragingival plaque control regimen of subjects presenting with chronic periodontitis.